Impact of COVID-19 on employment: sociodemographic, medical, psychiatric and neuropsychological correlates - Thompson, Madison; Ferrando, Stephen J.; Dornbush, Rhea; Lynch, Sean; Shahar, Sivan; Klepacz, Lidia; Smiley, Abbas (Frontiers in Rehabilitation Sciences, 2023)
Introduction Given the nature of the persistent physical and neuropsychiatric symptoms reported in the literature, among individuals after acute COVID illness; there is growing concern about the functional implications of the Post-Acute Sequelae of COVID-19 (PASC). We aim to evaluate associations of sociodemographic, medical, psychiatric and neuropsychological factors with employment status post COVID-19. Methods 59 participants were administered a neuropsychiatric assessment and queried about employment status and occupational difficulties months after quarantine. Two levels of comparison were conducted: (1) Those who took time off work (TTO) to those with no time off (NTO); (2) Those who reported occupational performance suffered (PS) to those who did not (PDNS). Results TTO vs. NTO exhibited extensive differences across medical, psychiatric and neurocognitive domains. PS vs. PDNS differed on subjective measures of physical and cognitive symptoms, but not on objective testing. Conclusion Individuals who took time off beyond COVID-19 quarantine experience persistent physical, psychiatric, subjective and objective neurocognitive burden. In contrast, occupational impairment appears to reflect subjective complaints, but not objective measures. Clinical implications are discussed.